(untitled) (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This study aims to describe the implementation of the Student Teams Achievement Division (STAD) model and analyze the improvement of student learning processes and outcomes in the History subject of Science and Science learning in fourth grade at SDN 09 Taluak. This study uses the Classroom Action Research (CAR) method with the Kemmis and McTaggart model which is implemented in two cycles, including the planning stage, action implementation, observation, and reflection. The research subjects consisted of 15 fourth grade students, the researcher as practitioner, and the class teacher as observer. Research data were collected through observation, documentation, and learning outcome tests, then analyzed using qualitative and quantitative descriptive analysis techniques. The results of the study show an increase in the quality of the learning process and student learning outcomes after the implementation of the STAD model. Learning planning increased from the good category in cycle I to very good in cycle II, followed by an increase in teacher and student activity during the learning process. Student learning outcomes also increased from the adequate category in cycle I to the good category in cycle II. These findings indicate that the implementation of the STAD model is able to increase student involvement in Science and Science learning and help students understand History material through more active and collaborative group learning activities.